Two Years Before the Mast - Dana, Richard Henry, 1815-1882 (Salt Lake City, UT : Project Gutenberg, 2003)
"Two Years Before the Mast" by Richard Henry Dana Jr. is a memoir published in 1840, based on his 1834-1836 voyage as a common sailor. Dana sailed from Boston around Cape Horn to Mexican California, trading for cow hides at mission ports along the coast. He vividly recounts shipboard life, witnessing brutal floggings, befriending Hawaiian sailors, and enduring treacherous Antarctic storms on the return journey. The work offers an unflinching look at maritime conditions and sailors' rights while capturing California before its transformation. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Two_Years_Before_the_Mast
There is an improved edition of this title, eBook #2055
See also PG#2055 with Introduction by Homer Eaton Keyes
Release date is 2003-07-01
Gutenberg submission by: David P. Steelman
Keywords: Seafaring life; Dana, Richard Henry, 1815-1882; Voyages and travels; Sailors